An analysis of Strategic Alliances in Automotive Industry: Case Study of Fiat-Tata Alliance and Fiat-Chrysler Alliance - Li, Mingke (2018)
The evolution of economic globalization undoubtedly promotes the strategic alliance among companies. The development of enterprises is no longer limited to national boundaries, but is seeking new ways to constantly expand themselves and adapt to the trend of economic integration. Initially, the main purpose of the cooperation between enterprises is to enter new markets, but gradually strategic alliances became the means for enterprises to constantly innovate in terms of marketing, technology and distribution. These phenomena also occur in automotive industry, which is an important industry to measure a country's development level and is the leading industry of economic globalization. An automotive company has different motivations when it enters different markets, and many theories such as resource-based view, can explain why companies use strategic alliances. In order to develop a successful strategic alliance, many factors need to be considered, such as economic, political and cultural environment, power relations between the two companies and technical differences.